PENGARUH KEPEMILIKAN MANAJERIAL, INSTITUSIONAL DAN PROPORSI DEWAN KOMISARIS INDEPENDEN PADA MANAJEMEN LABA - Mahadewi, A. A. Istri Sri; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi, 2017)
The purpose of this study was to determine the effect of managerial ownership, institutional ownership and the proportion of commissioners on earnings management. This research was conducted at all manufacturing companies in Indonesia Stock Exchange 2009-2013 period. The samples used as many as 33 companies from the population of 123 companies, through a purposive sampling method. The data collection is done by using the method of observation nonparticipant through the financial statements. The analysis technique applied is a technique of multiple linear regression analysis. The results show that partial managerial ownership, institutional ownership and the proportion commissioners significant negative effect on earnings management.
Keywords: Managerial Ownership; Institutional Ownership; The Proportion of Board Directors; Earnings Management